Alih Media Arsip Konvensional di Kantor Perpustakaan, Arsip, dan Dokumentasi Kota Bukittinggi - Wahyuni, Tri; Nst., Bakhtaruddin (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
Preparation of this paper aims to: (1) Knowing about the media than conventional filing in the Office of Libraries, Archives and Documentation of Bukittinggi. (2) Knowing the constraints that affect the transfer of conventional media file in the Office of Libraries, Archives and Documentation of Bukittinggi. To obtain information on the issue, conducted direct observation Perputakaan Office, Archives and Documentation of Bukittinggi and direct interviews with archivists. Conclusions are obtained as follows: (1) knowledge of the staff archivist in the technology field is very low. (2) Lack of equipment and technology as well as in the processing room archives inadequate. (3) Lack of funds and the budget of the government of Bukittinggi is the bottleneck in the implementation over conventional archival media. (4) As a center of information, education and research need to perform a wide range of businesses that should be planned, implemented as possible in making improvements to realize the function and purpose of the archive. Keywords: archive;Â  electronic medi; technology; knowledge